A review of computer-aided diagnosis in thoracic and colonic imaging - Suzuki, Kenji (Quantitative Imaging in Medicine and Surgery, 2012)
Medical imaging has been indispensable in medicine since the discovery of x-rays. Medical imaging offers useful information on patients’ medical conditions and on the causes of their symptoms and diseases. As imaging technologies advance, a large number of medical images are produced which physicians/ radiologists must interpret. Thus, computer aids are demanded and become indispensable in physicians’ decision making based on medical images. Consequently, computer-aided detection and diagnosis (CAD) has been investigated and has been an active research area in medical imaging. CAD is defined as detection and/or diagnosis made by a radiologist/physician who takes into account the computer output as a “second opinion”. In CAD research, detection and diagnosis of lung and colorectal cancer in thoracic and colonic imaging constitute major areas, because lung and colorectal cancers are the leading and second leading causes, respectively, of cancer deaths in the U.S. and also in other countries. In this review, CAD of the thorax and colon, including CAD for detection and diagnosis of lung nodules in thoracic CT, and that for detection of polyps in CT colonography, are reviewed.